Exploring creativity's complex relationship with learning in early elementary students. (June 2022) - Rubenstein, Lisa DaVia; Thomas, Jenna; Finch, W. Holmes; Ridgley, Lisa M.
Highlights: (3–5 bullet points, max 85 characters including spaces). Young students completed the Torrance Test of Creative Thinking-Figural (TTCT-F). Abstract: The purpose of this study was to examine the relationship between learning and creativity in early elementary students using both static and growth achievement scores in reading and mathematics. Participants were kindergarten and first grade students from the Midwestern United States. Initial correlations demonstrated significant positive relationships between students' performance on the Torrance Test of Creative Thinking –Figural (TTCT-F) and static academic achievement scores in both reading and mathematics, but that same relationship did not exist with academic growth scores. Specifically, when academic growth was examined further using Generalized Additive Models (GAMs), a complex picture emerged, such that grade level (i.e., kindergarten v. first grade) and subscale type (e.g., Fluency v. Originality) influenced the significance and nature of the relationship (i.e., linear v. nonlinear). In general, as students increased in creativity performance, they demonstrated less academic growth. Future work should explore the underlying mechanisms explaining these relationships to better help students leverage their creative abilities for positive academic gains in the classroom setting.